Dronedarone — an antiarrythmic agent with new potential for atrial fibrillation treatment - M. Yu. Gilyarov; V. A. Sulimov (Кардиоваскулярная терапия и профилактика, 2010)
Antiarrythmic therapy is one of the most problematic areas of modern medicine, with a constant search for new, more effective and safe medications. One of these new agents is dronedarone — a Class III antiarrythmic drug, with a structure similar to that of amiodarone, but without iodine in its molecule. Dronedarone interacts with different types of ion channels, and is at least as effective as amiodarone. At the moment, the dronedarone dosage of 400 mg twice a day is the best-studied therapeutic regimen for this medication. The paper analyses the results of published clinical trials of dronedarone, with the focus on ANDROMEDA and ATHENA studies. The former demonstrated that in patients with severe chronic heart failure, dronedarone increased all-cause mortality. The latter showed that in the dronedarone group, the combined incidence of cardiovascular death and cardiovascular hospitalisation was significantly lower than in the placebo group — 31,9 % vs. 39,4 %, respectively. In addition, dronedarone significantly reduced the annual risk of stroke — by 34 %, from 1,8 % to 1,2 % (p=0,027). Dronedarone safety could be regarded as satisfactory, with the majority of withdrawal cases due to such adverse effects as nausea and diarrhoea.